IMPLEMENTASI PROGRAM PEMBERDAYAAN PEREMPUAN DALAM MEWUJUDKAN KESETARAAN GENDER DI KABUPATEN KUTAI KARTANEGARA - Sitti Maimanah, Efri Novianto (Jurnal Borneo Administrator, 2015)
This research aimed to determine the implementation and the results achieved from the women's empowerment program in realizing gender equality in Kutai Kartanegara Regency. This type of research is qualitative deskriftif. Techniques used in determining the source of the data is Nonprobabilty Sampling by the method of Purposive Sampling. For the data collection Techniques used were participant observation, in-depth interviews, and study of the documentation. Data analysis techniques used to use interactive data analysis, as expressed by Miles and Huberman. Based on the results of the research can be inferred that the entire women's empowerment programs have been successfully implemented by the Agency for family planning, women's empowerment and child protection (BKBP3A) District of Kutai Kartanegara, just haven't managed to achieve gender equality in the district Kutai Kartanegara. Factors supporting the implementation of women's empowerment program in realizing gender equality in Kutai Kartanegara Regency, i.e. Regulation that support women's empowerment activities in realizing gender equality, namely Regulation of the Minister of Internal Affairs number 64 in 2011 and Regulation No. 52 Regent by 2013. While the factors restricting implementation of women's empowerment program is lack of budget allocated for financing women's empowerment program, quality of human resources in BKBP3A, limitations information, managing apparatus the attitude and lack ofsocialization.Keywords : Program Implementation, Empowerment of Women, Equality GenderPenelitian ini ditujukan untuk mengetahui implementasi dan hasil yang dicapai dari program pemberdayaan perempuan dalam mewujudkan kesetaraan gender di Kabupaten Kutai Kartanegara. Jenis penelitian ini adalah kualitatif deskriftif. Teknik yang digunakan dalam menentukan sumber data adalah nonprobabilty sampling dengan metode purposive sampling. Teknik pengumpulan data yang digunakan adalah dengan observasi partisipan, wawancara mendalam dan studi dokumentasi. Teknik analisis data yang digunakan menggunakan analisis data interaktif sebagaimana yang dikemukakan oleh Miles dan Huberman (1992:20). Berdasarkan hasil penelitian bisa disimpulkan bahwa seluruh program pemberdayaan perempuan telah berhasil di implementasikan oleh Badan Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak (BKBP3A) Kabupaten Kutai Kartanegara, hanya saja belum berhasil mewujudkan kesetaraan gender di Kabupaten Kutai Kartanegara. Faktor pendukung implementasi program pemberdayaan perempuan dalam mewujudkan kesetaraan gender di Kabupaten Kutai Kartanegara yaitu adanya regulasi yang mendukung kegiatan pemberdayaan perempuan dalam mewujudkan kesetaraan gender yaitu Peraturan Menteri Dalam Negeri Nomor 64 Tahun 2011 dan Peraturan Bupati Nomor 52 Tahun 2013. Sedangkan faktor penghambat implementasi program pemberdayaan perempuan adalah minimnya anggaran yang di al okasi kan unt uk membi ayai  program pemberdayaan perempuan, kualitas SDM di BKBP3A, keterbatasan informasi, sikap aparatur pelaksana dan kurangnya sosialisasi.Kata Kunci : Implementasi, Program Pemberdayaan Perempuan, Kesetaraan Gender